The role of the measurement and measurement equipment management system in the arms industry - Monika Bernatek; Mieczysław Jan Magierski (Nowoczesne Systemy Zarządzania)
Research objectives and hypothesis/research questions The aim of this paper is to present partial results of an experimental study on the influence of measurement uncertainty on gauges used at different stages of product manufacture. The authors will answer the problem questions: - What effect does a change in the standard, a change in the operator performing the measurement and environmental conditions have on the measurement result? - How do the results of gauge measurements affect the perception of products? A research hypothesis was formulated: it is assumed that the conditions and method of performing metrological confirmations of gauges have an impact on the quality and safety of manufactured products.